Ovarian Carcinoma With Isolated Spinal Cord Metastasis - Sarah Safadi MD; Patrick Rendon MD; Teresa Rutledge MD; Shadi Mayasy MD (Journal of Investigative Medicine High Impact Case Reports, 2016)
Ovarian cancer metastasis to the spinal cord is quite rare, and few case reports have been published previously. Herein, we present a case of a patient who was treated for ovarian cancer and was thought to be disease free for 17 months, then presented with lower limb weakness. She was found to have a T11-T12 metastatic intramedullary spinal cord lesion. On pathology, the diagnosis of metastatic ovarian adenocarcinoma was made. This report highlights the importance of maintaining a low threshold for ovarian cancer metastases to the spinal cord when patients present with neurologic sequelae, even in the setting of normal laboratory values, as early detection can prevent permanent neurological consequences.